2009
DOI: 10.1103/physrevb.79.125303
|View full text |Cite
|
Sign up to set email alerts
|

Atomic processes during Cl supersaturation etching ofSi(100)(2×1)

Abstract: Supersaturation etching starts with Cl insertion into Si-Si bonds of Si͑100͒ and leads to the desorption of SiCl 2 pairs. During etching, insertion occurs through a Cl 2 dissociative chemisorption process mediated by single dangling bond sites created by phonon-activated electron-stimulated desorption of atomic Cl. Based on scanning tunneling microscopy results, we identify a surface species, describe its involvement in supersaturation etching, and explore the energetics that control this process. In doing so,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…8 The activation barriers for Cl͑i͒ diffusion 22 and pairing 20 are 0.3-0.4 and 2.5 eV, respectively. The large barrier to pair hinders etching and results in an increase in Cl͑i͒ concentration with decreasing temperature, as demonstrated by Aldao et al 20 By reducing the temperature to 700-725 K, we have found a regime where diffusion is facile but pairing and terrace desorption of SiCl 2 are minimal. Accordingly, mobile Cl͑i͒ species can interrogate the surface and populate step sites.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…8 The activation barriers for Cl͑i͒ diffusion 22 and pairing 20 are 0.3-0.4 and 2.5 eV, respectively. The large barrier to pair hinders etching and results in an increase in Cl͑i͒ concentration with decreasing temperature, as demonstrated by Aldao et al 20 By reducing the temperature to 700-725 K, we have found a regime where diffusion is facile but pairing and terrace desorption of SiCl 2 are minimal. Accordingly, mobile Cl͑i͒ species can interrogate the surface and populate step sites.…”
supporting
confidence: 74%
“…Both display the inverse relationship with temperature seen for the concentration of Cl͑i͒. 20 Intriguingly, at 725 K the r-atom etch rate exceeds the nonrebonded step formation rate. Since etching produces nonrebonded steps, this suggests that some nonrebonded step units have reverted back to the rebonded structure despite the substantial energy preference, 1.8 eV/ a, for the former.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Essential information extracted from the publications is presented below. For halogen-based etching of GaAs, [48][49][50] silicon [51][52][53][54][55][56] and other materials there is a large body of atomistic etching work not aimed at pattern transfer and replacement of plasma etching methods. This literature provides important atomic layer etching and surface chemistry background, but is not reviewed.…”
Section: Atomic Layer Etching Of Various Materials -A Brief Surveymentioning
confidence: 99%
“…Over the years, people have been using halogen group (F, Cl, Br) plasma silicon material etching [4][5][6][7] . Searching Fluorine plasma etching mechanism of Si for improving the etching process to improve the etching efficiency, has a great significance.…”
Section: Introductionmentioning
confidence: 99%